Racial and ethnic variation in systemic lupus erythematosus and systemic sclerosis (scleroderma) - Fraser, Patricia (Henry Stewart Talks, 2007)
Epidemiology of lupus and scleroderma, Racial and ethnic variation in disease susceptibility and expression, Geographic variation, Environmental triggers, Hypothetical disease mechanisms of environmental triggers, Future research directions
Archived at 2021/02/25